Remote work as a new labor law institution - Pokutycka, Patrycja (Z Problematyki Prawa Pracy i Polityki Socjalnej, 2022)
The article concerns the topic of remote work. In the context of the COVID-19 pandemic, remote work has become a common solution, which has intensified the demands for its permanent introduction into the Polish law. Patrycja Pokutycka’s article compares remote work to the Labor Code’s regulations concerning teleworking. In addition, Pokutycka draws attention to what the regulations on remote work should look like in the future. Regulating remote work in the Labor Code would require a detailed analysis of the reasons for its introduction and the interests of both employers and employees.